The Maqāṣid approach and rethinking political rights in modern society - Safi, Louay (Intellectual Discourse, 2010)
This paper examines political rights in Islam by focusing on freedom of religion and the extent to which the state is empowered to enforce faith and religious law on society. It starts by comparing the notion of law in both Western and Islamic traditions, and then analyzes the difference between the ethical and legal within Sharī‘ah. The paper illustrates how Islamic law grew historically by working to limit the power of the state, and points out the need to maintain the distinction between the state and civil society for the proper implementation of Sharī‘ah. The paper also contends that those who call on the state to enforce all rules of Sharī‘ah on society rely on a faulty theory of right and concludes that Islamic law fully recognizes the right of individuals to adopt and practice their faith freely. Freedom of religion, it stresses, is an intrinsic aspect of Islamic law and all efforts to limit this freedom is bound to violate its purpose and dictates.